ANALISI KEBUTUHAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANDROID PADA MATERI SEBARAN FLORA DAN FAUNA INDONESIA DAN DUNIA KELAS XI SMA NEGERI 3 PADANG - Rusdi Arief; Ernawati Ernawati (JURNAL BUANA, 2021)
ABSTRACT This study aims to (1) determine the analysis of the needs of interactive learning media based on Android in the teaching and learning process (2) Knowing the ease of use of Geography learning media applications in class XI SMA Negeri 3 Padang. This research is a quantitative descriptive study, the research subjects are students of class XI IPS in Geography subject at SMA Negeri 3 Padang. The instrument used was a questionnaire, compiled using the help of google form and distributed through the class WhatsApp Group application. The sampling technique used Total Sampling with a total of 68 students as respondents. The results of this study indicate that the application of learning media based on Android GEO Explorer which is made has the highest priority frequency needs of 68 students, namely 45 students with a percentage of 66.17% in the "Medium" category and the use of the GEO Explore learning media application gets a percentage score of usability. amounting to 82.94%, from the questionnaire given to 68 students of class XI IPS in geography subjects with the results of the category "Very Appropriate" to be used as student needs in learning. Keywords: android based learning media needs, high school.